STRATEGI PENANGANAN SENGKETA TANAH STUDI KASUS : PT. MUSIM MAS DENGAN WARGA DUSUN TAMBUN KELURAHAN PANGKALAN LESUNG KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN TAHUN 2011-2013 - Arbi Alesandri; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Almost all aspects of yhe land will be triggeredand become a source of disputes such as problems with the boundaries of the land even a matter of dispute always synonymous with a dispute between the comunity and the company, such as then right to cultivate companies that exceed the permit Villagers Dusun Tambun with the students have done many demonstrations to government Pelalawan with the demands of freeing their hometown of status rights ofexploitation PT. Musim Mas, and demanded the government to review the district pelalawan to review the license right to cultivate PT. Musim Mas.The resultsof this study can show what the cause of land disputes PT. Musim Mas season wit Dusun Tambun fat and strategies Pelalawan local government in dealing with land disputes betweem PT. Musim Mas seasin with Dusun Tambun chubby dimples base villge. Regent decision KPTS number 140/pem/2012/31 to handle land disputes between PT. Musim Mas season with Dusun Tambun villagers fat. This is a strategic step taken by the government of the regency. Dispute relsolution team is formed with the task of addressing immediate dispute between PT. Musim Mas seasons with Dusun Tambun villagers fat.In this study the authors used qualitative methods, the data obtained and the data obtained are generally qualitative. this qualitative method attempts to understand and interpret the meaning of human interaction or human behavior in perspective according to the meaning of his own research. The results obtained are the steps Pelalawan strategy of government in resolving the dispute, with the formation of a team wich dispute that occur in the mortar between the base village PT. Muism Mas season Dusun Tambun villagers fat.Key Words : Strategy, Handling Disputes